Deskripsi Kemampuan Berbicara Pada Anak Kelompok Bermain di PAUD - Novita Mahmud; Rapi Us. Djuko; Setiyo Utoyo (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2023)
The purpose of this study was to describe the speaking ability of playgroup children at the Menara Ilmu PAUD, Limboto District, Gorontalo Regency. The method used in this research is descriptive qualitative. Data collection techniques used in the form of observation, interviews and documentation studies. Based on the research results, the description of the ability to speak in playgroup children at the Menara Ilmu PAUD is optimal. This is evidenced by the fact that the child is able to talk about the events that are happening around him, is able to speak according to his way of thinking and the child is able to speak in the process of thinking and has full appreciation. This cannot be separated from the hard work of a teacher and parental guidance for children in the ability to speak well.